Cooling induces phase separation in membranes derived from isolated CNS myelin - Pusterla, Julio Martín (2017)
Purified myelin membranes (PMMs) are the starting material for biochemical analyses such as the isolation of detergent-insoluble glycosphingolipid-rich domains (DIGs), which are believed to be representatives of functional lipid rafts. The normal DIGs isolation protocol involves the extraction of lipids under moderate cooling. Here, we thus address the influence of cooling on the structure of PMMs and its sub-fractions. Thermodynamic and structural aspects of periodic, multilamellar PMMs are examined between 4C and 45C and in various biologically relevant aqueous solutions. The phase behavior is investigated by small-angle X-ray scattering (SAXS) and differential scanning calorimetry (DSC). Complementary neutron diffraction (ND) experiments with solid-supported myelin multilayers confirm that the phase behavior is unaffected by planar confinement. SAXS and ND consistently show that multilamellar PMMs in pure water become heterogeneous when cooled by more than 10–15C below physiological temperature, as during the DIGs isolation procedure. The heterogeneous state of PMMs is stabilized in physiological solution, where phase coexistence persists up to near the physiological temperature. This result supports the general view that membranes under physiological conditions are close to critical points for phase separation. In presence of elevated Ca2+ concentrations (> 10 mM), phase coexistence is found even far above physiological temperatures. The relative fractions of the two phases, and thus presumably also their compositions, are found to vary with temperature. Depending on the conditions, an “expanded” phase with larger lamellar period or a “compacted” phase with smaller lamellar period coexists with the native phase. Both expanded and compacted periods are also observed in DIGs under the respective conditions. The observed subtle temperature-dependence of the phase behavior of PMMs suggests that the composition of DIGs is sensitive to the details of the isolation protocol.